FAKTOR PASIEN BERHUBUNGAN DENGAN ANGKA READMISSION PADA PELAKSANAAN DISCHARGE PLANNING PASIEN ACUTE CORONARY SYNDROME (ACS) - Romalina, Romalina; Indra, M Rasjad; Susmarini, Dian (Unusa Press, 2017)
Acute Coronary Syndrome’s (ACS) patient has a risk getting readmission in 30 – 45 days after come back from hospital. Discharge planning has purpose to guaranty continuity of treatments’ qualities among of hospital with communities’ service. The purpose of this thesis is to determine patients’ and nurses’ factors that have contributing to the rate of readmission in doing discharge planning of ACSs’ patients in RSUD Dr. Saiful Anwar Malang. The design of this thesis is a prospective observational analytic approach. The experiment was conducted in August to October 2014 in RSUD Dr. Saiful Anwar Malang. The sample is consisted of 60 families of ACS’s patients with using consecutive sampling approach. The collecting of data uses questionnaire’s sheet. The data analysis uses logistics’ regretting with backward method. The predictors’ factors of the readmission rate of Acute Coronary Syndrome (ACS) patients are the complication of the hearth failure and diabetes mellitus diseases. Health professionals need to pay attention to prevention effort to provide education to patients and families. The educational materials is in the form of the modification of risk factors (smoking, alcohol, blood pressure, personal weight, nutrition, activity, exercise, stress) and modification management as recommended.